IMPLEMENTASI NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM KEGIATAN KHUTBATUL IFTITAH - Sumiatin Sumiatin; Ulli Tiyas Rachmawati; Saiful Ihwan; Sugiyar Sugiyar (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Multicultural education is education that helps students to develop the ability to recognize, accept, appreciate and celebrate cultural diversity. At the Wali Songo Ngabar Islamic Boarding School, these multicultural values are manifested through the annual assembly activities within the framework of the santri introduction week. The purpose of this study is to identify the supporting factors for multicultural activities that are going well. This study uses a qualitative method with an ethnographic approach. Collecting data in this study was carried out by interviews, observation, and documentation. This research was conducted through 3 stages namely observation, data analysis, and drawing conclusions. The results of this study found several things which were summarized into 3 important points supporting factors for best practice multicultural education at the Wali Songo Ngabar Islamic Boarding School, Ponorogo, namely (1) Awareness of differences; (2) Harmony and peace; (3) Motivation. These supporting factors need to be maintained so that other multicultural activities can be implemented better